In Vivo Plasminogen Deficiency Reduces Fat Accumulation - Hoover-Plow, Jane; Ellis, Jill; Yuen, Lawrence (Thrombosis and Haemostasis, 2002)
Obesity and non-insulin dependent diabetes are associated with a decrease in fibrinolysis, which is mediated by the plasminogen system. The purpose of the current study was to investigate the role of the plasminogen system in the reduced body weight of the plasminogen deficient (Plg−/−) mice. In this study we have found that the reduced body weight in Plg−/− mice is due to a reduced rate of the adipose tissue (25% less) and whole body fat (30% less) accumulation during growth in Plg−/− compared to wild-type (WT) littermates. When the mice are fed a high fat-lipogenic diet, adipose tissue accumulation increases in the Plg−/− mice indicating that the capacity for lipid filling of cells was not blocked. In addition, glycerol phosphate dehydrogenase, a marker of late differentiation, was not different in the depots from WT and Plg−/− mice. The number of stromal cells (number × 105/g adipose tissue), isolated from inguinal (Plg−/− 3.4 ± 1.2, n = 6; WT 0.17 ± 0.07, n = 7, p < 0.02) and gonadal (Plg−/− 11.0 ± 0.4, n = 6; WT 3.1 ± 0.7, n = 7, p < 0.05) fat depots, was markedly higher in the depots from the Plg−/− mice than WT mice. Differentiation of stromal cells in culture from the Plg−/− mice was reduced compared to cells from WT mice. These results suggest that differences in the stromal cell population are responsible for the reduced adipose tissue accumulation in the Plg−/− mice, and that the plasminogen system plays an important role in adipose tissue accumulation.
Keywords: Plasminogen; gene-targeted mice; adipose tissue; growth